KOMPARASI IMPLEMENTASI PENYALURAN PROGRAM SEMBAKO DI KOTA METRO: HIMPUNAN BANK NEGARA (HIMBARA) VS PT POS - Aulia Rahmawati; Muhammad Ardiansyah (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2023)
Food Social Assistance in Indonesia has been transformed several times, beginning with Welfare Rice, Non-Cash Food Assistance (BPNT) to Sembako Program. The transformation of food social assistance is carried out to find a better formulation in supplying food needs with balanced nutrition for the poor and vulnerable. The Sembako Program in Metro City has been implemented since 2018 and distributed by Himbara, BRI Bank with e-Warong as a place for utilization of assistance (disbursement and distribution). Furthermore, in 2022 based on Kepdirjen PFM number 29 of 2022 determines that the Sembako Program is distributed in cash by PT Pos Indonesia. This study has compared the distribution of the sembako program by Himbara and PT Pos in Metro City. The purpose of this research is to find similarities and differences to know which implementation is better. The method in this research is descriptive qualitative with a comparative approach. The findings of this research are that the distribution of the Sembako Program in Metro City is more effective when distributed by Himbara with e-Warong as a place to utilize the assistance. On the other hand, there are community empowerment targets in the distribution of sembako programs by Himbara, such as empowerment of e-Warong members. Keywords: Sembako Program; Comparison; Empowerment; E-Warong.